Interaction of Crohn's disease susceptibility genes in an Australian paediatric cohort. - Josef Wagner (Public Library of Science (PLoS), 2010)
Genetic susceptibility is an important contributor to the pathogenesis of Crohn's disease (CD). We investigated multiple CD susceptibility genes in an Australian paediatric onset CD cohort. Newly diagnosed paediatric onset CD patients (n = 72) and controls (n = 98) were genotyped for 34 single nucleotide polymorphisms (SNPs) in 18 genetic loci. Gene-gene interaction analysis, gene-disease phenotype analysis and genetic risk profiling were performed for all SNPs and all genes. Of the 34 SNPs analysed, four polymorphisms on three genes (NOD2, IL23R, and region 3p21) were significantly associated with CD status (p<0.05). All three CD specific paediatric polymorphisms on PSMG1 and TNFRSF6B showed a trend of association with p<0.1. An additive gene-gene interaction involving TLR4, PSMG1, TNFRSF6B and IRGM was identified with CD. Genes involved in microbial processing (TLR4, PSMG1, NOD2) were significantly associated either at the individual level or in gene-gene interactive roles. Colonic disease was significantly associated with disease SNP rs7517847 (IL23R) (p<0.05) and colonic and ileal/colonic disease was significantly associated with disease SNP rs125221868 (IBD5) and SLC22A4 & SLC22A4/5 variants (p<0.05). We were able to demonstrate genetic association of several genes to CD in a paediatric onset cohort. Several of the observed associations have not been reported previously in association with paediatric CD patients. Our findings demonstrate that CD genetic susceptibility in paediatric patients presents as a complex interaction between numerous genes.